A model for measuring the internet banking interface quality - Siddig, Mahgoub Elradi Ahmed (2018)
Internet Banking Service Quality (IBSQ) measurement is still an evolving research area in the field of service quality measurement. Service quality measurement still remains one of the competitive strategies for Internet banking (IB) service providers in order to achieve higher performance and an increase in adoption by users. IBSQ provides platform for evaluating services provided by IB service providers based on consumption experience(s). Literature study conducted shows that the existing IBSQ measurement models includes different Service Quality (SQ) dimensions, which are insufficient in measuring Internet Banking Interfaces (IBIs) service quality. Thus, user experience for ensuring customer satisfaction, user–friendliness, and loyalty due to lack of human face–to–face communication are not adequately measured. Moreover, these models do not have mechanism that provide adequate response to particular concerns and requests of individual users. In addition to IBIs service quality measurement associated problems, different existing methodological approaches used in the development of IBSQ measurement models, also have their associated problems. Thus, in this research work, we propose a method that have a holistic and rigorous measurement model that addresses such limitations. The proposed model address the associated problems with IBSQ measurement by analyzing, identifying and categorizing those dimensions for measuring IB services quality, which have an impact on users’ attitudes and intentions for continuous use of IBIs. An empirical study using a survey questionnaire was conducted among 494 respondents from IB users to validate the IBSQ dimensions, and further propose the Internet Banking Interface Quality Model (IBIQM). In this respect, two different tests were carried out to validate the proposed model. The first test carried out was targeted towards collecting feedback from experts while the second test collect responses from end-users. The prototyped interface was evaluated using an extended Technology Acceptance Model (TAM) test that make use of a survey conducted among 23 undergraduate students. This extended TAM test comprises of five main constructs, which include perceived enjoyment, perceived ease of use, perceived usefulness, attitude toward, and intention to use interface. The results of the empirical study demonstrates the validity of the proposed model. The prototype was validated by an experts from academics and professionals in the banking sector. The result of expert review confirmed the applicability of prototyped interface for the future development of IBIs. This research shed light on the improvement of IBSQ in a way to effectively evaluate IBIs with Malaysia context as an empirical case study. According to the performance limitations of the SQ dimensions, an IBIQM was proposed with an emphasis on Virtual Reality (VR) integration as an effective solution.